BNI Syariah Sebelum Pandemi Covid 19 Ditinjau Dari Prediksi Financial Distress - Yuwita Ariessa Pravasanti; Yudi Siyamto (Nur Science Institute, 2022)
In terms of the ratio of financing to third party funds, BNI Syariah has experienced a significant decline over the last 5 years. If this decline is not immediately resolved, it will be disrupted and the possibility of financial distress in banking can occur. The purpose of the study was to determine the financial distress experienced by BNI Syariah before the pandemic, namely 2016-2019. The research method used in this research is descriptive quantitative approach with calculations using modified Z-Score analysis. The results showed that in the last quarter of March 2016 to September 2018 before the COVID-19 pandemic, BNI Syariah was categorized as a gray area with a Z-Score value of 1.1 < Z